Spontaneous Fire Risk Rating of a Colliery Proposed to be Developed by Short Wall Method of Mining - Nandy D. K; Banerjee D. D; Sen S. K (The Australasian Institute of Mining and Metallurgy, 1988)
It has been stressed that the intrinsic spon- taneous heating characteristics of a coal is not enough in predicting spontaneous fire risk of a mine. The influence of extraneous conditions created from the system of mining operations are also to be reckoned with, A case study was made with a mine in Jharia field, India, being proposed to be developed under short wall method with complete extraction in 4-5 slices followed by stowing.